value Study Of Import Fruit Value Chain From Importers To Wholesale Traders At PT. Segar Makmur Lestari: value chain - Panggabean, Laura Ester; Wibisono, Totok (International Journal of Social and Management Studies, 2022)
Fruit is not currently a food to be consumed by many people. One of the companies engaged in fruit procurement is PT. Segar Makmur Lestari as an importer of fruit in Semarang City. Currently, sales of PT. Segar Makmur Lestari are fluctuating and tend to decline which implies a decline in competitive competence, so that researchers are interested in studying the Value Chain Study of Imported Fruits from Importers to Wholesalers at PT. Segar Makmur Lestari. The research was carried out using qualitative methods. The informants in this study were employees of PT. Segar Makmur Lestari and their customers (Wholesale Traders). Collecting data through in-depth interviews, reviews literature and documentation and analysis using data reduction, triangulation and pulled conclusions The results of the research are the stages of the value chain at the company, there are seven supply activities, namely: orders to foreign importers, arrival information, goods receipt, goods storage and stock taking, providing information to customers, receiving orders from customers, and shipping goods to customers. Value Chain at PT. Segar Makmur shows good condition, through cost reduction in each supply chain process so as to obtain a cost advantage that is intended to achieve the company's competitive advantage.